Study of novel ?5-cyclopentadienyl and ?6-arene platinum group metal complexes containing a N4-type ligand and their structural characterization - Gupta, Gajendra; Yap, Glenn P. A.; Therrien, Bruno; Rao, Kollipara Mohan (My University, 2009)
The mononuclear ?5-cyclopentadienyl complexes [(?5-C5H5)Ru(PPh3)2Cl], [(?5-C5H5)Os(PPh3)2Br] and pentamethylcyclopentadienyl complex [(?5-C5Me5)Ru(PPh3)2Cl] react in the presence of 1 equiv. of the tetradentate N,N'-chelating ligand 3,5-bis(2-pyridyl)pyrazole (bpp-H) and 1 equiv. of NH4PF6 in methanol to afford the mononuclear complexes [(?5-C5H5)Ru(PPh3)(bpp-H)]PF6 ([1]PF6), [(?5-C5H5)Os(PPh3)(bpp-H)]PF6 ([2]PF6) and [(?5-C5Me5)Ru(PPh3)(bpp-H)]PF6 ([3]PF6), resp. The dinuclear ?5-pentamethylcyclopentadienyl complexes [(?5-C5Me5)Rh(?-Cl)Cl]2 and [(?5-C5Me5)Ir(?-Cl)Cl]2 as well as the dinuclear ?6-arene ruthenium complexes [(?6-C6H6)Ru(?-Cl)Cl]2 and [(?6-p-iPrC6H4Me)Ru(?-Cl)Cl]2 react with 2 equiv. of bpp-H in the presence of NH4PF6 or NH4BF4 to afford the corresponding mononuclear complexes [(?5-C5Me5)Rh(bpp-H)Cl]PF6 ([4]PF6), [(?5-C5Me5)Ir(bpp-H)Cl]PF6 ([5]PF6), [(?6-C6H6)Ru(bpp-H)Cl]BF4 ([6]BF4) and [(?6-p-iPrC6H4Me)Ru(bpp-H)Cl]BF4 ([7]BF4). However, in the presence of 1 equiv. of bpp-H and NH4BF4 the reaction with the same ?6-arene ruthenium complexes affords the dinuclear salts [(?6-C6H6)2Ru2(bpp)Cl2]BF4 ([8]BF4) and [(?6-p-iPrC6H4Me)2Ru2(bpp)Cl2]BF4 ([9]BF4), resp. These compds. have been characterized by IR, NMR and mass spectrometry, as well as by elemental anal. The mol. structures of [1]PF6, [5]PF6 and [8]BF4 have been established by single crystal x-ray diffraction studies and some representative complexes have been studied by UV-vis spectroscopy. [on SciFinder(R)]
Keywords: cyclopentadienyl arene ruthenium iridium pyridyl pyrazole complex prepn structure; osmium rhodium cyclopentadienyl pyridyl pyrazole complex prepn; crystal mol structure cyclopentadienyl arene ruthenium iridium pyridyl pyrazole